Playful frames : styles of widescreen cinema - Rybin, Steven, 1979- (Techniques of the Moving Image Series., 2023)
"A widescreen frame in cinema beckons the eye to playfully, creatively roam. Such technology also gives inventive filmmakers room to disrupt and redirect audience expectations, surprising viewers through the use of a wider, more expansive screen. Playful Frames: Styles of Widescreen Cinema studies the poetics of the auteur-driven widescreen image, offering nimble, expansive analyses of the work of four distinctive filmmakers - Jean Negulesco, Blake Edwards, Robert Altman, and John Carpenter - who creatively inhabited the nooks and crannies of widescreen moviemaking during the final decades of the twentieth century. Exploring the relationship between aspect ratio and subject matter, Playful Frames shows how directors make puckish use of widescreen technology. All four of these distinctive filmmakers reimagined popular genres (such as melodrama, slapstick comedy, film noir, science fiction, and horror cinema) through their use of the wide frame, and each brings a range of intermedial interests (painting, performance, and music) to their use of the widescreen image. This study looks specifically at the technological underpinnings, aesthetic shapes, and interpretive implications of these four directors' creative use of widescreen, offering a way to reconsider the way wide imagery still has the potential to amaze and move us today"--